(untitled) (JULACE: Journal of the University of Namibia Language Centre, 2018)
The purpose of this study was to explore the role of drama in teaching English to enhance students’ communicative skills at the University of Namibia. The discussions of the research focused on assessing the benefits of using drama in the teaching of English to increase students’ motivation and self-confidence, as well as to enhance their communicative skills. Research findings revealed the effectiveness of drama oriented English lessons to the benefits of students’ speaking skills, motivation, self-esteem and confidence in their abilities to communicate in English. In addition, the findings revealed that drama activities aided students develop a community and foster group cohesiveness, which helped in building students’ confidence when speaking English in front of their classmates. Moreover, the study results revealed that motivation is linked to self-confidence as the drama activities accorded students the opportunity to use the target language in real life situations.